2021
DOI: 10.1038/s41598-021-82387-x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen induces shift in abundances of specific groups of the coral microbiome

Abstract: Synthetic estrogens such as ethinylestradiol (EE2) are persistent micropollutants that are not effectively removed from wastewater by conventional treatments. These contaminants are released into waterbodies, where they disrupt endocrine systems of organisms and cause harmful effects such as feminization, infertility, reproduction problems and genital malformations. The consequences of this pollution for key marine ecosystems such as coral reefs and their associated microbiomes are underexplored. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…The results showed that several classes of bacteria varied dynamically but remained dominant in different treatment groups, including Gammaproteobacteria and Alphaproteobacteria . E1 elicited a subsidy to the bacteria belonging to these classes, which could be supported by previous research regarding the bacterial degradation of estrogen ( Balcom et al, 2016 ; Mainetti et al, 2021 ; Vilela et al, 2021 ). The variation of bacterial community structure in water samples from different locations may be mainly due to the composition of the bacterial community structure in the in-situ water sample ( Ji et al, 2017 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that several classes of bacteria varied dynamically but remained dominant in different treatment groups, including Gammaproteobacteria and Alphaproteobacteria . E1 elicited a subsidy to the bacteria belonging to these classes, which could be supported by previous research regarding the bacterial degradation of estrogen ( Balcom et al, 2016 ; Mainetti et al, 2021 ; Vilela et al, 2021 ). The variation of bacterial community structure in water samples from different locations may be mainly due to the composition of the bacterial community structure in the in-situ water sample ( Ji et al, 2017 ).…”
Section: Discussionsupporting
confidence: 82%
“…These interference effects were assessed using several laboratory-scale microcosm or mesocosm experiments ( Yergeau et al, 2012 ; Guasch et al, 2016 ). Studies have also investigated the ecological mechanisms controlling microbial community assemblies and interspecies interactions in rivers, which have been disturbed anthropogenically ( Gad et al, 2020 ; Mainetti et al, 2021 ; Vilela et al, 2021 ). It has been suggested that estrogens and other endocrine disruptors have contrasting ecological effects on the aquatic microbiology community.…”
Section: Introductionmentioning
confidence: 99%
“…Ethinyl-estradiol (EE2) is another estrogen receptor agonist that has been tested in zebrafish. EE2 is a synthetic derivative of endogenous E2 and, due to its wide use as a constituent in oral contraceptives, reaches aquatic environments through wastewater effluents ( Vilela et al, 2021 ); agricultural and aquaculture runoff are other sources ( Tang et al, 2021 ). EE2 concentration in surface waters varies, ranging up to 62 ng/L ( Versonnen and Janssen, 2004 ), and it is consistently identified worldwide make it a serious environmental contaminant ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall bacterial diversity was assessed by hightrough-put sequencing using the platform Illumina MiSeq (Illumina, San Diego, CA, USA at the Argonne National Laboratory, http://ngs.igsb.anl.gov (accessed on 2 March 2017), Lemont, IL, USA) with paired-end strategy, following the manufacturer's guidelines. The raw sequences were processed using Mothur v.1.39.1 software [68], as described in [69]. Briefly, Greengenes database (version from August 2013) was used with an 80% confidence threshold, and sequences classified as Chloroplasts, Mitochondria, Archaea, Eukarya, or not assigned to any kingdom were removed.…”
Section: Bacterial Composition By 16s Rrna Gene Sequencingmentioning
confidence: 99%